WANITA PEDAGANG LOPEK BUGI (STUDI PERUBAHAN NILAI ADAT KAMPAR DI DESA PALUNG RAYA) - Elfi Zarni; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research is entitled "Women Traders Lopek Bugi (Study of Changes in the Traditional Value of Kampar in Palung Raya Village." This study aims to identify the characteristics of lopek bugi traders, determine the motivation of women to work as lopek bugi traders and analyze the form of changes in the value of girls. The research method used in this research is the qualitative research method with a survey approach and sampling with purposive sampling. The subjects in this study amounted to 5 people, namely Kampar girls who are in charge of serving buyers and are unmarried and key informants 3, namely traditional leaders from the Putopang tribe. , malay, and mandailiong. Based on the results of the study, the characteristics of the age 15 to 23 years. With junior high school and high school education. Their motivation to work is first: economic conditions to help the family economy, second: leisure time is time that is not used for work after working on p homework, third: prestige or joining in, that is, they see their friends working while they are not working. The changes that have occurred here are the changing roles of girls, who previously worked to take care of the house or the domestic sector, now they have changed to work in the informal sector, especially as lopek bugi traders.Keywords: Traders, Girls, Change in value